Water Stress, Irrigation and Concentrations of Pentacyclic Triterpenes and Phenols in Olea europaea L. cv. Picual Olive Trees - Raquel Jiménez-Herrera; Beatriz Pacheco-López; Juan Peragón (MDPI AG, 2019)
Pentacyclic triterpenes and phenols are two types of bioactive molecules found in olive trees that have important activities related to health and disease prevention. Triterpenes, including oleanolic acid, maslinic acid, erythrodiol and uvaol, show antitumoral activities, and phenols such as oleuropein, tyrosol, and hydroxytyrosol are natural antioxidants. The concentration of these metabolites is considered a marker of the quality of olives and olive oil. In recent years, a lack of rain water has caused important economic losses relating to olive trees grown in Jaén, Spain. In this work, we investigated the effect of water stress by drought on the concentration of pentacyclic triterpenes and phenols in the fruits, leaves, stems and roots of cv. Picual olive trees, by comparing the concentration found in water-stressed versus irrigated plants. We used HPLC-UV/Vis and HPLC-MS to identify and determine the concentration of each individual compound. Our results showed that important changes in the concentration of these compounds are produced in response to water stress in different organs. The total content of most of these compounds in the fruits was significantly reduced, affecting their quality and production.